Trico strike badge, 1976 (1976)
1976 1960-2000 "Trico strike badge, 1976" [T0405.jpg], 1976 In 1976, there was an equal pay strike at the Trico-Folberth windscreen wipers factory at Brentford Middlesex. The women organised by the Amalgamated Union of Engineering Workers, were out for 21 weeks before winning their demand to be paid the same basic rate as the men.